Benefits and limitations of animal models in partial bladder outlet obstruction for translational research. (1st October 2017) - Kitta, Takeya; Kanno, Yukiko; Chiba, Hiroki; Higuchi, Madoka; Ouchi, Mifuka; Togo, Mio; Moriya, Kimihiko; Shinohara, Nobuo
Abstract: The functions of the lower urinary tract have been investigated for more than a century. Lower urinary tract symptoms, such as incomplete bladder emptying, weak urine stream, daytime urinary frequency, urgency, urge incontinence and nocturia after partial bladder outlet obstruction, is a frequent cause of benign prostatic hyperplasia in aging men. However, the pathophysiological mechanisms have not been fully elucidated. The use of animal models is absolutely imperative for understanding the pathophysiological processes involved in bladder dysfunction. Surgical induction has been used to study lower urinary tract functions of numerous animal species, such as pig, dog, rabbit, guinea pig, rat and mouse, of both sexes. Several morphological and functional modifications under partial bladder outlet obstruction have not only been observed in the bladder, but also in the central nervous system. Understanding the changes of the lower urinary tract functions induced by partial bladder outlet obstruction would also contribute to appropriate drug development for treating these pathophysiological conditions. In the present review, we discuss techniques for creating partial bladder outlet obstruction, the characteristics of several species, as well as issues of each model, and their translational value.